Hubungan Pencemaran Partikel Terampai (PMIO) dengan Pesakit Asma - Hashim, Zalina; Jalaluddin, Juliana; Zainal Abidin, Azman; Omar, Azizi (Universiti Putra Malaysia Press, 1996)
A study of 30 asthmatic children was conducted in Kuala Lumpur. The objective of this study was to examine the relationship between respirable particulates (PMIO) and asthma attacks. This study was conducted from 1st September to 31st December 1994. Patients were selected from the Pediatric Unit, Kuala Lumpur General Hospital. Questionnaires were used to obtain information on the history and severity of asthma attacks of these patients. Diary cards were used to collect information on the frequency of asthma attacks. The patients' progress was followed through every week during the study period and the attacks recorded. The data on air quality and meteorology were collected from the Universiti Pertanian Malaysia air quality monitoring station located at the Kuala Lumpur City Hall. Based on the interviews, parents perceived that the causal factors of asthma attacks were cold weather (73.3%), air pollution (70%), and diet (67.7%). Statistical tests indicated that there was a significant relationship between asthma attacks and the PM10 concentration (r~0.73) throughout the study period. During the haze episode, the relationship between asthma attacks and PMIO concentrations was more significant (r = 0.86).